Cytomegalovirus-associated gastric ulcer: a diagnostic challenge in a patient of fulminant hepatitis with steroid pulse therapy. (30th August 2013) - Tamura, Jiro; Arakaki, Shingo; Shibata, Daisuke; Maeshiro, Tatsuji
Abstract : A 69-year-old woman presented with malaise. She had had organising pneumonia with the treatment of prednisolone. A diagnosis of fulminant hepatitis was made and steroid pulse therapy was initiated. Ten days later, a colonic resection with a colostomy was performed because of the perforated diverticulitis of the sigmoid colon. She presented with epigastric pain and melena after surgery. Despite the administration of the proton pump inhibitor, an endoscopy revealed multiple deep, punched-out ulcers of the stomach. Biopsy specimen showed cytomegalovirus (CMV) infection. The melena and CMV antigenemia was improved with ganciclovir; however the patient died from worsening of hepatic failure. We emphasise that CMV-associated gastric ulcers should be considered in the differential diagnosis of gastric ulcers in patients treated with immunosuppressive drugs.